Optimization and comparative analysis of hybrid renewable energy systems for sustainable and clean energy production in rural Cameroon considering the loss of power supply probability concept - Yemeli Wenceslas Koholé; Clint Ameri Wankouo Ngouleu; Fodoup Cyrille Vincelas Fohagui; Ghislain Tchuen (Energy Conversion and Management: X)
This study investigates a hybrid photovoltaic (PV) / wind turbine system integrated with thermal energy storage (TES) and pumped-hydro energy storage (PHES) as a sustainable and reliable power solution for remote areas. The optimization of PV/Wind/TES and PV/Wind/PHES systems is performed for a commercial building in Kousseri, Cameroon, focusing on minimizing the system’s net present cost (NPC) while meeting the load demand. Three meta-heuristic algorithms namely, the water evaporation optimization, Cuckoo Search Algorithm (CSA), and teaching–learning-based optimization are applied, and the results are compared in terms of NPC, excess energy fraction, electricity demand fulfillment, and CO2 emission reduction. System reliability is assessed using the maximum allowable loss of power supply probability, with values set at 0%, 2%, 5%, and 10%. The results indicate that the CSA algorithm outperforms the others, with the PV/Wind/TES configuration being the most cost-effective, followed by PV/TES, Wind/TES, PV/Wind/PHES, PV/PHES, and Wind/PHES systems. Additionally, the Wind/PHES system is identified as the most reliable and efficient in reducing CO2 emissions, making it a superior alternative to conventional fossil fuel-based power plants.